Evidence for a cryptic 46, XX cell line in a 45, X/46, X, psu idic(Xq) patient with normal reproduction. Issue 12 (December 1997) - James, R S; Sharp, A J; Cockwell, A E; Coppin, B; Jacobs, P A
Abstract : Gonadal dysgenesis resulting in primary infertility is one of the most common features of Turner syndrome. There have been a number of cases described of pregnancy in 45, X subjects, but whether or not the fertility is associated with a 46, XX cell line in the germ cells is not known. We describe a 45, X/46, X, psu idic(Xq) female with normal fertility, in whom a cryptic 46, XX cell line was found in the germ cells.